Moving Forward With Changing Times: ODL as a way to further education opportunities - The, Star (The Star, 2019)
Open and distance learning (ODL) has been a boon for many people, from working professionals to people with physical disabilities. With advancing technology, it has become easier to pursue education through ODL.